2020
DOI: 10.1002/ejoc.202000363
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of 7‐Membered Heterocyclic Compounds

Abstract: The work presented herein describes the synthesis of a formerly inaccessible class of heterocyclic compounds. The reaction relies on α‐phthalimido‐amides, which are readily prepared from amino acids in 2 simple reactions steps. Under amide activation conditions in which classical keteniminium ions are not formed, the nitrile solvent is incorporated into the new fused 7‐membered ring system. Due to the absence of a keteniminium intermediate, the stereogenic information in the α‐position is fully retained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“… [16] For this reason, a range of substituted pyridines is commonly surveyed when optimising reactions involving electrophilic amide activation. [ 12 , 15 ] However, in certain circumstances, the presence of base can even prohibit the desired reactivity. This was observed by Maulide et al.…”
Section: Electrophilic Amide Activationmentioning
confidence: 99%
See 2 more Smart Citations
“… [16] For this reason, a range of substituted pyridines is commonly surveyed when optimising reactions involving electrophilic amide activation. [ 12 , 15 ] However, in certain circumstances, the presence of base can even prohibit the desired reactivity. This was observed by Maulide et al.…”
Section: Electrophilic Amide Activationmentioning
confidence: 99%
“…In 2020, Maulide et al reported the use of triflic anhydride for the synthesis of unusual 7membered fused heterocycles 21 from α-phthalimido-amides 20 (Scheme 5). [15] From a mechanistic point of view, electrophilic activation takes place at the amide, which is more nucleophilic than the tethered imide. This activation is thought to trigger intramolecular attack by the imide, resulting in formation of an oxazolinium ion 22.…”
Section: Ipso-activation Of Amidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Maulide et al reported the use of triflic anhydride for the synthesis of unusual 7membered fused heterocycles 21 from α-phthalimido-amides 20 (Scheme 5). [15] From a mechanistic point of view, electrophilic activation takes place at the amide, which is more nucleophilic than the tethered imide. This activation is thought to trigger intramolecular attack by the imide, resulting in formation of an oxazolinium ion solvent of this reaction, was then proposed to yield ketenimine 23, before a two-step ring expansion closed the 7-membered ring, yielding 21 after isomerisation and hydrolysis.…”
Section: Ipso-activation Of Amidesmentioning
confidence: 99%
“… 7 And most of the studies conducted revealed that cycloheptane and its derivatives, such as 1,4-dioxepane, 1,3-dioxepane, 6,7-dihydro-SH-1, etc., mostly prefer the chair, twist-chair, or twist-boat conformations depending on the position and presence of a heteroatom or double bonds in the molecular structure. 7 , 8 In another study conducted by Dillen, 9 a holistic conformational analysis of azepane, oxepane, silepane, phosphepane, thiepane, and the azepanium cation was carried out by high-level electronic structure calculations, and the results compared appropriately with those of the well-known cycloheptane. The twist-chair conformation was the most stable conformation reported for the studied systems, and the chair conformation was mostly associated with the transition state.…”
Section: Introductionmentioning
confidence: 99%